2018
DOI: 10.2494/photopolymer.31.451
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Photosensitive Dielectric Materials for Advanced Packaging Applications

Abstract: Hitachi Chemical DuPont MicroSystems (HDMS) is a supplier of photosensitive negative-tone polyimides (PI) and positive-tone poly(benzoxazole)s (PBO) for use as protection layers in semiconductor ICs or as dielectrics for re-distribution layers in Fan-in or Fan-out wafer level packages. These materials offer an easy manufacturing process as well as ensuring high reliability in semiconductor packages. Recently, design rules and structures for next generation packages are advancing in order to achieve higher end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hence, photosensitive organic materials with low residual stress have been developed as interlayer dielectrics for semiconductor devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, Shoji et al had reported that a photosensitive preimidized polyimide (PI) with low residual stress is developed by introducing special soft segment and utilizing low temperature curable crosslinker [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, photosensitive organic materials with low residual stress have been developed as interlayer dielectrics for semiconductor devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, Shoji et al had reported that a photosensitive preimidized polyimide (PI) with low residual stress is developed by introducing special soft segment and utilizing low temperature curable crosslinker [2].…”
Section: Introductionmentioning
confidence: 99%
“…7 also shows applicable photosensitive materials for fabrication in PoP packages.Photosensitive materials include resists used in LSI manufacturing, bump forming resists, insulating materials for RDL (Redistribution Layers), and photosensitive films for Cu plating. Photosensitive insulating materials for RDL have been reported from several companies[11][12][13][14]. Polymer-related materials include a film for release layer acting temporary adhesive, encapsulant materials, die bonding film etc.…”
mentioning
confidence: 99%